Reading self-concept, trait emotional intelligence and anxiety of primary school children with dyslexia - Polychroni, Fotini; Antoniou, Alexandros-Stamatios; Kofa, Olga; Charitaki, Garyfalia (Frontiers in Education, 2024)
The association between the cognitive and the affective domain in reading is well documented in research, especially when difficulties are manifested. The aim of the present study was a) to investigate levels of reading self-concept, trait emotional intelligence and anxiety of students with dyslexia and compare them to students with no previous assessment and b) explore the hypothesis that reading self concept and trait emotional intelligence are negative predictors of state and trait anxiety taking into account students' individual characteristics such as gender, school year and school performance.Methods: A total of 794, 5 th and 6 th grade Greek primary school children aged 10 to 12 years old participated in the study. Of them fifty children had a statement of dyslexia. The State and Trait Anxiety Inventory for Children, the Reading Self Concept Scale and the Trait Emotional Intelligence Questionnaire-Short Form were administered to the participants.Results: The results showed that children with dyslexia were more vulnerable in terms of their perceptions of reading self concept and emotional intelligence as compared to typical peers. Moreover, students' characteristics i.e., grades in math and language and dyslexia had a direct positive path to trait emotional intelligence and reading self concept while trait emotional intelligence and reading self-concept predicted negatively anxiety.Discussion: The implications of the results in terms of the possible protective role of reading self concept and emotional intelligence on anxiety for children with dyslexia are discussed and suggestions for future research are presented..